TRADISI PENYEMBELIHAN HEWAN PADA ACARA KEMATIAN MASYARAKAT BATAK MANDAILING DI DESA SOSOPAN KECAMATAN PADANG BOLAK KABUPATEN PADANG LAWAS UTARASUMATERA UTARA - Septiana Harahap; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The research was conducted in Sosopan Village, Padang Bolak District, North Padang Lawas Regency, North Sumatra. With the aim of knowing the history behind the customary process and the meaning of the tradition of slaughtering animals at the event of the death of the Mandailing Batak people in Sosopan Village. The method used is descriptive qualitative method. Data collection techniques using observation techniques, in-depth interviews, and documentation. The results of this study concluded that the customary process of slaughtering animals at the death ceremony of the Mandailing Batak people in Sosopan Village consisted of several stages, namely, Paboahon (providing grief news information), Makkobar adat (customary deliberations), animal slaughter, mutual cooperation, manariangkon, mangabisi ari, wirid, khotom, mambatu kubur. Then the meaning of the tradition of slaughtering animals at the event of death can be seen from the animals being slaughtered. If the buffalo is slaughtered then it can carry out the customary makkobar for laying the customary title of the person who died to his heirs, can set up a yellow traditional umbrella as a sign of royal descent or symbol of the message of the person who died, if the animal is a ox that is slaughtered then the custom that can be carried out is only establish a traditional umbrella, while for the Goat it can only be a medium for carrying out aqiqah for people who have died. Keywords: Mandailing Batak, Death, Animal Slaughte